Responsibility and the Brain Sciences - De Brigard, Felipe (Ethical theory and moral practice, 2008)
Some theorists think that the more we get to know about the neural underpinnings of our behaviors, the less likely we will be to hold people responsible for their actions. This intuition has driven some to suspect that as neuroscience gains insight into the neurological causes of our actions, people will cease to view others as morally responsible for their actions, thus creating a troubling quandary for our legal system. This paper provides empirical evidence against such intuitions. Particularly, our studies of folk intuitions suggest that (1) when the causes of an action are described in neurological terms, they are not found to be any more exculpatory than when described in psychological terms, and (2) agents are not held fully responsible even for actions that are fully neurologically caused.